Effects of scale and strain rate on the tensile behaviors of large-rupture-strain fiber-reinforced polymers (LRS-FRP). (30th May 2023) - Zhao, Debo; Zhang, Jiewei; Ye, Zenghui; Fei, Jianbo; Li, Jiwei
Highlights: Tensile behaviors of LRS-FRP at different scales were experimentally investigated. LRS-FRP sheets were tested with a high-speed hydraulic servo system. A dynamic tensile constitutive model of LRS-FRP was established. Abstract: A comprehensive understanding of the dynamic material properties of LRS-FRP/epoxy laminates at high strain rates is urgently needed for guiding the design and performance evaluation of LRS-FRP strengthening structures under dynamic loadings. In this study, quasi-static tensile tests of LRS-FRP at different scales (single filament, fiber bundle, FRPs with single and five bundles) were first conducted and the experiment results showed that size effect and existence of resin matrix had marked influences on tensile behaviors of LRS-FRP. Then, LRS-FRP sheets whose scale were close to engineering applications, were tested with a high-speed hydraulic servo system to investigate their tensile behaviors at varying stain rates. The variation tendencies of key mechanical parameters, such as tensile strength, elastic and secondary tangent moduli, and toughness, were analyzed based on the experimental results. The dynamic tensile behaviors of PEN-FRP/PET-FRP showed obvious strain rate effects at the strain rate ranging from 0.0001 s −1 to 100 s −1 . The strengths at the turning point of PEN/PET-FRP at a strain rate of 100 s −1 reached more than twice the values at quasi-static loading, while the amplification of ultimate strengths with strain rate increasing from 0.0001 s −1 to 100 s −1 was about 20 %. Empirical formulas of dynamic increase factor for LRS-FRPs are derived and a dynamic tensile constitutive model of LRS-FRP is finally established.